TriCalm® hydrogel is significantly superior to 2% diphenhydramine and 1% hydrocortisone in reducing the peak intensity, duration, and overall magnitude of cowhage-induced itch - Papoiu ADP; Chaudhry H; Hayes EC; Chan YH; Herbst KD (Dove Medical Press, 2015)
Alexandru DP Papoiu,1 Hunza Chaudhry,2 Erin C Hayes,2 Yiong-Huak Chan,3 Kenneth D Herbst4 1Independent contractor, San Diego, CA, USA: 2Cosmederm Bioscience, Inc., San Diego, CA, USA; 3Biostatistics Unit, Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 4Department of Medicine, University of California, San Diego, San Diego, CA, USA Background: Itch is one of the most frequent skin complaints and its treatment is challenging. From a neurophysiological perspective, two distinct peripheral and spinothalamic pathways have been described for itch transmission: a histaminergic pathway and a nonhistaminergic pathway mediated by protease-activated receptors (PAR)2 and 4. The nonhistaminergic itch pathway can be activated exogenously by spicules of cowhage, a tropical plant that releases a cysteine protease named mucunain that binds to and activates PAR2 and PAR4. Purpose: This study was conducted to assess the antipruritic effect of a novel over-the-counter (OTC) steroid-free topical hydrogel formulation, TriCalm®, in reducing itch intensity and duration, when itch was induced with cowhage, and compared it with two other commonly used OTC anti-itch drugs. Study participants and methods: This double-blinded, vehicle-controlled, randomized, crossover study recorded itch intensity and duration in 48 healthy subjects before and after skin treatment with TriCalm hydrogel, 2% diphenhydramine, 1% hydrocortisone, and hydrogel vehicle, used as a vehicle control. Results: TriCalm hydrogel significantly reduced the peak intensity and duration of cowhage-induced itch when compared to the control itch curve, and was significantly superior to the two other OTC antipruritic agents and its own vehicle in antipruritic effect. TriCalm hydrogel was eight times more effective than 1% hydrocortisone and almost six times more effective than 2% diphenhydramine in antipruritic action, as evaluated by the reduction of area under the curve. Conclusion: TriCalm hydrogel has a robust antipruritic effect against nonhistaminergic pruritus induced via the PAR2 pathway, and therefore it could represent a promising treatment option for itch. Keywords: antipruritic treatment, nonhistaminergic pruritus, head-to-head comparison